PERMINTAAN KREDIT INVESTASI DI INDONESIA (2002:1-2009:12) - , Selvi Herry; , Prof. Dr. Nopirin, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Banking as one of the intermediation function, role in encouraging economic growth and expand employment opportunities through the provision of funds and the channeling of credit. According to Law No.7/1992 on Banking which has been amended in Law no. 10/1998, credit is the provision of money or bills or its equivalence, based on a borrowing contract between banks and other parties, which obliges the borrower to repay the debts after a certain period of time with interest. The data released by Bank Indonesia shows that the growth of investment credit is lower than the growth of consumer credit. The low investment credit growth reflects that the credit funds in the banking sector can not be fully utilized as a source of investment financing and production for the real sector (industry and services). The purpose of this study is to analyze the impact of GDP growth, investment growth, inflation, real interest rates and real exchange rate on the demand for investment credit in Indonesia. This study made use of monthly data for the period of January 2002 to December 2009. First, the variables were tested by using unit root tests to test the stationary of those variables and then followed by Johansen cointegration test to identify whether those variables have a longterm relationship or only a short-term one. The variables were then modeled based on Vector Autoregressive (VAR) model and Vector Error Correction Model (VECM) and then analyzed the Impulse Response Function (IRF) and the Variance Decomposition (VD) of the VAR model. The result of the analysis shows that the GDP has a positive and significant impact on the demand for investment credit in Indonesia while the inflations has a negative and significant impact on the demand for investment credit in Indonesia. The result indicates that 1 percent increase in GDP will increase the demand for investment credit by 3.5 percent. The increase in investment of 1 percent will increase the demand for investment credit by 0.03 percent. An increase in inflation by 1 percent will decrease the investment credit by 0.7 percent, and an increase of real interest rate for credit by 1 percent will decrease the investment credit by 0.02 percent. The result also shows that the increase of real exchange rate by 1 percent will decrease the investment credit by 0.7 percent. Therefore, this study concludes that good economic conditions can increase economic growth and therefore contributes positively to the demand for investment loans, thereby increasing the demand for investment credit. The inflation rate has a negative and significant impact of the demand for investment credit, meaning that the less volatile price could decrease the demand for investment credit. The investment positively affect on the demand for investment credit while the real interest rates for credit and real exchange rates negatively affect the demand for investment credit but not significant.